The Influence of Information Transparency and Brand Trust on Purchase Decisions for the “Boost Juice” Product - Keysha Aulea Hamada; Erlita Ridanasti (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to analyze the influence of product health information transparency and brand trust on purchasing decisions for Boost Juice. The research was conducted on consumers at Yogyakarta, with a sample of 105 respondents selected through purposive sampling. A quantitative approach was used, applying multiple linear regression analysis to examine both the partial and simultaneous effects of the independent variables on purchasing decisions. The descriptive analysis showed that the average score for information transparency was 32.86 and for brand trust was 32.39, both reflecting positive consumer perceptions. The purchasing decision variable had an average score of 32.64, indicating strong consumer tendencies to choose Boost Juice. Partially, product health information transparency had a positive and significant effect on purchasing decisions, with a coefficient of 0.252 and a significance value of 0.003. Brand trust showed a stronger influence, with a coefficient of 0.676 and a significance value of 0.000. Simultaneously, both variables significantly influenced purchasing decisions, as evidenced by an F-statistic of 97.442 (p = 0.000). The model explains 65% of the variation in purchasing decisions (Adjusted R² = 0.650). These findings support Relationship Marketing Theory, emphasizing that transparency in information and strong brand trust are essential in building long-term relationships with customers and encouraging purchasing decisions for healthy beverage products.